Propuesta de planeación estratégica para la empresa Samaria Tours S.A.S. en Cartagena de indias - Colombia. (2022)
Samaria Tours S.A.S. is an operator and travel agency located in the city of Cartagena dedicated to sales of touristic services. Actually, the company shows different problems derived from Covid -19 effects and post pandemic among others factors have affected in a negative way. Due to all these reason this paper work developed a strategic plan based on an applied investigation. With all this information was possible to gathered, a strategic diagnosis is elaborated where the external and internal environment of the organization is analyzed using tools such as the five forces of Porter, the Pestel analysis, the Canvas analysis, the matrix of internal factors and the Stakeholder matrix which is possible to identify the opportunities, threats, weaknesses and strengths of the company. After this, evaluation and formulation of the strategic addressing are done where the mission, vision, values, policies and objectives are established, seeking to adapt to the real needs of the Organization and taking into account the opinion of the Direction and Collaborators, later strategic planning is designed, proposing the strategies and actions necessary to carry it out and to achieve the objectives of the organization, which is possible to achieved, applying a SWOT analysis and action plans, finally, suggestions and tools are provided such as the balanced scorecard and the strategic map, to monitor the fulfillment of the objectives and facilitating the dissemination of the strategies.